Conversão de registros em XML para MARC 21: um modelo baseado em folhas de estilo XSLT - Assumpção, Fabrício Silva [UNESP] (2013)
MARC 21 Formats are metadata standards internationally used for records interchange in bibliographic domain. Despite the importance of the MARC 21 Formats and other international metadata standards, there are integrated library systems that use their own metadata standard. The non-use of international metadata standards decreases the possibilities of records interchange and it might cause problems during data migration between systems. In face to the integrated library systems that do not use international metadata standards, our research question is the conversion of the records from these systems to MARC 21 records. In order to be read, MARC 21 records must be coded in such a way that allows informatics applications to recognize the record content. The technologies used for this codification have evolved from traditional ISO 2709 standard to Extensible Markup Language (XML). The use of XML in the codification gave us the possibility to use transformation stylesheets created with Extensible Stylesheet Language for Transformation (XSLT) for the records conversion. Considering the need of records conversion and the possibilities brought by XML, we aim to develop a model for conversion of records that were created with different metadata standards and are coded in XML to MARC 21 records using XSLT stylesheets. For this purpose, we made a literature review about record conversion, MARC 21 Formats, ISO 2709, XML, XSLT and MARCXML. We highlighted the main issues on the use of the XML for documents codification and the possibilities provided by XSLT. In order to discuss the relation between MARC 21 and XML, we presented MARCXML markup language. Starting from the literature review, we developed a model for record conversion and described its components and its steps, as well as its validation through the use in the conversion of bibliographic records from Personal Home Library (PHL) integrated library systems. In conclusion, we highlighted the characteristics of the model and we summarized some issues related to the use of the model and to the instruments that came from the application of the model in the PHL records conversion.